Effects of population density and snow depth on the winter diet composition of sika deer. Issue 2 (February 2015) - Seto, Takayuki; Matsuda, Naoko; Okahisa, Yuji; Kaji, Koichi
ABSTRACT: The understanding of population density and weather effects is fundamental for evaluating the population dynamics of ungulates. However, studies focusing on temporal variations in diet composition are limited. We investigated the effects of population density and snow depth on variation in the winter diet composition of 2 contrasting sika deer ( Cervus nippon ) populations in Oku‐Nikko and Ashio, Tochigi Prefecture, central Japan by monitoring diet composition for ≥15 years. The main food in Oku‐Nikko was dwarf bamboo ( Sasa nipponica ), which has a high crude protein content. This plant sometimes had low availability because of the combination of snow accumulation and reduced culm height associated with chronic grazing. The main food in Ashio was Japanese pampas grass ( Miscanthus sinensis ), which has a low crude protein content, but its availability was high because of high culm height and little snow accumulation. In Oku‐Nikko, snow accumulation and high deer density negatively affected the proportion of dwarf bamboo found in rumen contents, with the most significant effect found in calves. In Ashio, Japanese pampas grass composed a relatively high and constant proportion of the rumen contents when snow accumulation was ≤50 cm; however, it was negatively affected by snow accumulation of >50 cm. In addition, the utilization of Japanese pampas grass was reduced only when deer density was extremely high (>150 deer/km 2 ). Our results clearly demonstrate that absolute density is not the sole factor that affects variation in the winter food selection of sika deer. The combined effects of snow depth and habitat quality, such as vegetation height, are overwhelmingly important in determining the winter diet composition of sika deer populations. © 2015 The Wildlife Society.